2004
DOI: 10.1093/hmg/ddh146
|View full text |Cite
|
Sign up to set email alerts
|

GABRD encoding a protein for extra- or peri-synaptic GABAA receptors is a susceptibility locus for generalized epilepsies

Abstract: A major challenge in understanding complex idiopathic generalized epilepsies has been the characterization of their underlying molecular genetic basis. Here, we report that genetic variation within the GABRD gene, which encodes the GABAA receptor delta subunit, affects GABA current amplitude consistent with a model of polygenic susceptibility to epilepsy in humans. We have found a GABRD Glu177Ala variant which is heterozygously associated with generalized epilepsy with febrile seizures plus. We also report an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(214 citation statements)
references
References 25 publications
4
206
1
3
Order By: Relevance
“…183 Mutations involving the ␥2 subunit in two cases associated with GEFSϩ and in two cases associated with childhood absence epilepsy with febrile convulsions have been found to alter the kinetic properties of the receptor and also their surface expression. 183 Three mutations in families with GEFSϩ involving the ␦ subunit 185 are associated with reduced current, suggesting that impairment of tonic inhibition by extrasynaptic GABA receptors can also produce epilepsy. Studies in genetically modified mice have revealed spontaneous seizures in ␤3 knockout mice, 186 supporting the interpretation that the seizures that are a prominent feature of the Angelman syndrome (which, in addition to other genetic abnormalities, lacks the ␤3 gene) are due specifically to defects in GABA A receptors.…”
Section: Cys-loop Ligand-gated Channelsmentioning
confidence: 99%
“…183 Mutations involving the ␥2 subunit in two cases associated with GEFSϩ and in two cases associated with childhood absence epilepsy with febrile convulsions have been found to alter the kinetic properties of the receptor and also their surface expression. 183 Three mutations in families with GEFSϩ involving the ␦ subunit 185 are associated with reduced current, suggesting that impairment of tonic inhibition by extrasynaptic GABA receptors can also produce epilepsy. Studies in genetically modified mice have revealed spontaneous seizures in ␤3 knockout mice, 186 supporting the interpretation that the seizures that are a prominent feature of the Angelman syndrome (which, in addition to other genetic abnormalities, lacks the ␤3 gene) are due specifically to defects in GABA A receptors.…”
Section: Cys-loop Ligand-gated Channelsmentioning
confidence: 99%
“…Recent studies have demonstrated that defects in receptor function or tonic inhibition resulted in neurological disorders such as epilepsy [349,350]. Studies regarding the genetics of human epilepsy demonstrated that various heritable mutations in GABA A receptor subunits are associated with epilepsy [351].…”
Section: Gaba Receptorsmentioning
confidence: 99%
“…Listing only those involving the Na V family and associated subunits; GEFS + Type 1 is associated with mutations to SCN1B encoding the β 1 subunit of Na V ; GEFS + Type 2 with SCN1A encoding Na V 1.1; and GEFS + Type 7 with SCN9A encoding Na V 1.7. [68][69][70] The phenotypes associated with the various GEFS + mutations vary between affected individuals, but the most common symptoms are febrile seizures (FS). As mentioned previously, FS are quite common in young children and have an age dependent decrease in prevalence.…”
Section: Gefs +mentioning
confidence: 99%